Bourdieu's metanoia : seeing the social world anew - Grenfell, Michael, 1953- (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, 2023)
"Bourdieu once commented that what was needed was a 'new gaze' on the social world - a metanoia. This book describes this view and how to do it. Based on biographical detail and the socio-political contexts, which surrounded him, it sets out his vision of society and culture. Grounded on the distinction between traditional and modern worlds, it shows how ethnographic experience led Bourdieu to an intellectual epiphany. It shows the growth of his conceptual tools and the emergence of 'field theory' in various contexts: Law, Religion, Fashion, Sport, Culture, Fine Art, Philosophy, Literature, and Politics. The book offers an up-to-date, extensive account of Bourdieu, his work and its significance. It centres on philosophical questions of social experience and intellectual practice. Based around his entire oeuvre, it features recent posthumous publications in French, providing important insights for the first time into his way of viewing the world. Including issues of the State, Neoliberalism, and resistance this book explores how the social, philosophical and political came together for Bourdieu to shape how we see ourselves, and our place in the contemporary world - a metanoia. As both an introductory and advanced text, it is a valuable resource for both the newcomer to Bourdieu and the experienced researcher. It will be of interest to undergraduates, postgraduates, researchers of Bourdieu's work in the areas of Sociology, Media, Philosophy, Religion, Economics, Architecture, Cultural Studies, Education, Music, Journalism, Gender Studies, Politics, the Law, Fine Arts, and Linguistics"--
Keywords: Bourdieu, Pierre, -- 1930-2002.; Sociology -- France -- History -- 20th century; Civilization, Modern -- 20th century -- Philosophy; SOCIAL SCIENCE / Sociology / General